Whole exome sequencing aids the diagnosis of Simpson–Golabi–Behmel syndrome in two male fetuses. Issue 1 (January 2020) - Xiang, Jingjing; Zhang, Qin; Song, Xiaoyan; Liu, Yinghua; Li, Haibo; Li, Hong; Wang, Ting
Objective: To diagnose and explore the genetic aetiology of Simpson–Golabi–Behmel syndrome type 1 (SGBS1) in two male fetuses. Methods: Prenatal ultrasound scans and further genetic analysis using karyotype analysis, chromosomal microarray analysis, whole exome sequencing (WES) and Sanger sequencing were conducted. Results: Prenatal ultrasound scans of two fetuses showed multiple congenital anomalies and hydramnios. Subsequent to termination of the pregnancies, a novel nonsense variant (c.892G>T, p.E298*) in the glypican 3 ( GPC3 ) gene of the two fetuses was identified by WES and further confirmed by Sanger sequencing. The two fetuses were diagnosed with SGBS1. The mother was heterozygous for the c.892G>T variant. Conclusion: This study describes the prenatal sonographic features of SGBS1, emphasizes the role of WES in the diagnosis of SGBS1 and expands the known mutation spectrum of the GPC3 gene.